Base‐Promoted Double‐Bond‐Migration/Hydrolysis/Isomerization of 4‐Aryl‐1, 1, 1‐trifluorobut‐2‐en‐2‐yl Trifluoromethanesulfonates: A Metal‐Free Approach to β‐Trifluoromethyl Ketones. Issue 45 (14th November 2018) - Zhou, Yuhan; Zhang, Chunxia; Zhao, Yilong; Li, Dong; Zhao, Jinfeng; Wang, Zhaotian; Qu, Jingping
Abstract : A method for the synthesis of β‐trifluoromethyl ketones promoted by a base is described. In the presence of DBU, 1‐aryl‐4, 4, 4‐trifluoromethylbutanones with various functional groups were obtained through the reaction of 4‐aryl‐1, 1, 1‐trifluorobut‐2‐en‐2‐yl trifluoromethanesulfonates with water in moderate to excellent yields. The reaction underwent a double‐bond‐migration/hydrolysis/isomerization pathway, and 1‐aryl‐4, 4, 4‐trifluorobut‐2‐en‐1‐ols were determined as the key intermediates. Both electron‐withdrawing and electron‐donating groups, such as fluoro, chloro, bromo, ester, cyano, trifluoromethyl, alkyl, and alkoxy, were tolerated well in this reaction. Abstract : A metal‐free synthesis of 1‐aryl‐4, 4, 4‐trifluoromethylbutanones has been developed. Promoted by DBU, 4‐aryl‐1, 1, 1‐trifluorobut‐2‐en‐2‐yl trifluoromethanesulfonates were converted into 1‐aryl‐4, 4, 4‐trifluoromethylbutanones smoothly in moderate to excellent yields.